Passively Q-switched Er:YAG laser at 1645 nm utilizing a multilayer molybdenum ditelluride (MoTe2) saturable absorber. (13th July 2018) - Liang, Yangyang; Zhao, Jia; Qiao, Wenchao; Yang, Kejian; Li, Tao; Zhao, Shenzhi
Abstract: An MoTe2 saturable absorber (SA) was fabricated for mid-infrared laser operations. By using this type of home-made SA as a Q-switcher for an in-band pumped Er:YAG laser, stable pulse trains with an average output power of 1.14 W were obtained at an absorbed pump power of 10.51 W. The Q-switched pulse envelope had a repetition rate of 41.59 kHz and its pulse duration was measured to be 1.048 µ s, corresponding to a pulse energy of 27.4 µ J and a peak power of 26.14 W.